THE RELATIONSHIP OF THE ROLE OF PARENTS WITH ONLINE LEARNING DURING THE COVID-19 PANDEMIC AT HEALTH INSTITUE DELI HUSADA DELI TUA - Mona Fitri Gurusinga; Afrilius Simanjuntak (Jurnal Penelitian Keperawatan Medik, 2022)
Introduction: In this online learning, the role of parents becomes bigger. If online, parents usually only accompany learning to supervise. In these cases, parents must be the teacher for their children. Objective: to find out the relationship between the role of parents and online learning during the COVID-19 pandemic at Deli Husada Deli Tua health institute in 2021 Research Methods: This type of research uses quantitative research with a cross sectional research design, which was conducted on 30 parents whose children are doing online learning at home. The role of parents in online learning Based on the table of cross tabulation of the relationship between the role of parents and online learning during the COVID-19 pandemic at Deli Husada Deli Tua health institute in 2021 Research Results: The role of parents is very good with online learning very good as many as 7 people (46.7%), the role of parents is very good with online learning is quite good 8 people (53.3%), the role of parents is very good with learning Poor online 0 (0.0%),The role of parents is quite good with online learning very good as many as 2 people (20.0%), the role of parents is quite good with online learning is good enough as many as 6 people (60.0%), the role of parents is quite good with online learning is not good as many as 2 people (20.0%), the role of parents is not good with online learning very good as much as 1 (20.0%), The role of parents is not good with online learning is quite good as many as 3 (60.0%), the role of parents is not good with online learning is not good as much as 1 person (20.0%).Based on the results of statistical tests and data processing using chi square calculations with the help of SPSS version 21 for windows, the P value = 0.002 (P < 0.05) Conclusion: it can be concluded that there is a significant relationship between the relationship between the role of parents and online learning in Deli Husada Deli Tua health institute in 2021.